Handbook of Performability Engineering - Misra, Krishna B. (Springer, 2017)
Performability engineering provides us with the framework to consider both dependability and sustainability for the optimal design of products, systems or services. Whereas dependability is an aggregate of one or more of the attributes of survivability (such as quality, reliability, and maintainability etc.) and safety, and the present designs based on dependability and life cycle costs cannot be really called truly optimal since these attributes are strongly influenced by the design, raw materials, fabrication, techniques and manufacturing processes employed, and their control and usage (...)